Physical Violence Against Children During the Covid-19 Pandemic - Katayane, Carlo Jean; Titahelu, Juanrico Alfaromona Sumarezs (SANISA: Jurnal Kreativitas Mahasiswa Hukum, 2023)
Introduction: Children are a vulnerable group that needs to be protected from all acts of crime and violence in accordance with statutory provisions so that their rights are fulfilled, especially during the pandemic. The Covid-19 pandemic also has an impact on acts of violence against children. During the Covid-19 pandemic, there were many acts of violence against children, as obtained from the Women and Children Protection Unit (PPA) of the Ambon Island and Lease Islands City Police, there was an increase in cases of physical violence against children, namely in 2020 there were 5 cases of reports that entered the PPA Polresta then in 2021 it increased to 10 cases against children in the form of physical violence.Purposes of the Research: The research method used is normative research, statutory approach, primary and secondary legal materials and material collection procedures using literature studies.Results of the Research: Factors causing physical violence in children during the Covid-19 pandemic include (1) Environmental factors, where the lack of control functions from the family causes children to mingle incorrectly so that it can result in things that are negative to the child; (2) Age factors, where the age of the child is also very important because many children who are not mature enough according to the statutory category do not understand well about violence and (3) Family factors where children lack attention from both parents so it is very easy for children to seek attention in ways such as committing violence against their fellow friends.